2020
DOI: 10.1002/ijc.33306
|View full text |Cite
|
Sign up to set email alerts
|

Impact of DNA damage repair defects and aggressive variant features on response to carboplatin‐based chemotherapy in metastatic castration‐resistant prostate cancer

Abstract: Platinum-based chemotherapy is not standard of care for unselected or genetically selected metastatic castration-resistant prostate cancer (mCRPC) patients. A retrospective assessment of 71 patients was performed on platinum use in the Netherlands. Genetically unselected patients yielded low response rates. For a predefined subanalysis of all patients with comprehensive next-generation sequencing, 30 patients were grouped based on the presence of pathogenic aberrations in genes associated with DNA damage repai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 34 publications
(74 reference statements)
0
24
0
Order By: Relevance
“…The killing effect of carboplatin is cell apoptosis induced by DNA damage ( 13 ). Therefore, to further explore the effect of PSMD4 on carboplatin sensitivity of EOC cells, flow cytometry was performed.…”
Section: Resultsmentioning
confidence: 99%
“…The killing effect of carboplatin is cell apoptosis induced by DNA damage ( 13 ). Therefore, to further explore the effect of PSMD4 on carboplatin sensitivity of EOC cells, flow cytometry was performed.…”
Section: Resultsmentioning
confidence: 99%
“…Men harboring DDR gene mutations had shorter time to CRPC than those with wild type DDR genes (7.3 months vs not reached; p = 0.01). 41 Patients with DDR gene mutations have poor response to ADT alone and combination of ADT with platinum-based chemotherapy 42 or PARP inhibitors 43 would be beneficial for patients with DDR gene mutations.…”
Section: Future Perspectivementioning
confidence: 99%
“…Cisplatin and carboplatin were shown to exert moderate activity in men with mCRPC (38,39). Retrospective studies revealed that platinum-based chemotherapy was more effective in patients with mCRPC harboring BRCA mutations (Table II) (40)(41)(42)(43). The PSA responses (>50% decline) to platinum were 64%-100% and 17%-36% in BRCA2 mutation carriers and non-carriers, respectively.…”
Section: Are Parp Inhibitors Going To Dramatically Change the Treatment Landscape Of Mcrpc?mentioning
confidence: 99%